2016
DOI: 10.1159/000446451
|View full text |Cite
|
Sign up to set email alerts
|

Urinary [TIMP-2]·[IGFBP7] - Novel Biomarkers to Predict Acute Kidney Injury

Abstract: Background: Urine microscopy is an established technique to assess kidney disease, and can add valuable information about the mechanism of damage. However, it requires the time and expertise of an experienced nephrologist and, therefore, is typically used for a limited number of patients in practice. A rapid biomarker test that identifies patients from the emergency department (ED) who are likely to have positive urine microscopy findings would enable more efficient use of this technique. Methods: Four hundred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 27 publications
0
13
0
1
Order By: Relevance
“…The initial literature search found 103 potentially relevant articles, and among them, 24 articles that seemingly met our inclusion and exclusion criteria were downloaded for further perusal. Finally, a total of 10 articles written in English and published between 2014 and 2016 were considered in this meta-analysis [ 11 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial literature search found 103 potentially relevant articles, and among them, 24 articles that seemingly met our inclusion and exclusion criteria were downloaded for further perusal. Finally, a total of 10 articles written in English and published between 2014 and 2016 were considered in this meta-analysis [ 11 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine of ten studies ( n = 1597) were conducted in adult participants, and one study ( n = 51) in children [ 14 ]. Six studies ( n = 350) were conducted to evaluate the diagnostic value of urinary [TIMP-2] x [IGFBP7] for AKI after major surgeries (5 cardiac surgery [ 13 , 14 , 16 18 ] and 1 non-cardiac surgery [ 15 ]), and four studies ( n = 1298) were conducted among ICU patients [ 11 , 12 , 19 , 20 ]. The definition of AKI in eight studies accorded with the Kidney Disease: Improving Global Outcomes classification (KDIGO) criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Durch Spezialfärbungen können eosinophile Leukozyten in Einzelfällen angefärbt werden. leicht messbare Biomarker im Urin, die mit höheren Tubulusnekrose-Scores assoziiert sind [9].…”
Section: Leukozytenunclassified
“…Many studies have shown that the product of the concentration of these proteins TIMP2·IGFBP7 in urine (Astute Medical, San Diego, CA, USA) is an early indicator of risk for AKI. [23][24][25][26][27][28] As the first available AKI biomarker test in the USA, urinary TIMP2·IGFBP7 was cleared in 2014 by the US FDA. 29 In this study, we tested the hypothesis that urinary TIMP2·IGFBP7 collected directly prior and after PBC administration can predict the development of AKI.…”
Section: Introductionmentioning
confidence: 99%